PORTFOLIO BASED INSTURUCTION THE PERSPECTIVE AND RESPONSE IN TEACHING WRITING FOR SECONDARY HIGH SCHOOL IN MAKASSAR (AN EXPERIMENTAL STUDY) - Dewi Nopitasari; Imran Trista Udin Tristan (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The objectives of this research were to find out the teachers’ perception towards the portfolio based instruction, the data were collected through interview with the senior teacher, an experimental research was applied for this research. The research took place at SMA Negeri 5 Makassar and the data were analyzed using descriptive and inferential statistics and the result of the research shows the response of the teacher toward the application or the implementation of portfolio based instruction that The strange of this portfolio because it gives the teacher response about how to measure the progress of the students although the time may be next time it’s mean long time to make teacher remember the students’ have progress when I teach last time now, they can increase, they can improve their knowledge for example writing. By explanation portfolio assessment, it really important student ability, especially in English. And make the teacher to remember the progress of the students step by step. So, at the last time teacher easier to give mark of the student, by seeing for the first time the teacher asks to the students, at last process the students study starting from beginning until the last the teacher can give the students in real mark for the students.